Synthesis of Nano-Photocatalyst ZnO-Natural Zeolite to Degrade Procion Red - Tuty Emilia Agustina; Elda Melwita; David Bahrin; Rianyza Gayatri; Indah Fitriany Purwaningtyas (International Journal of Technology, 2020)
The development of textile factories has had a significant impact on the environment because dye wastewater is difficult to degrade. The handling of textile wastewater usually involves the adsorption method, in which pollutants only transfer to another phase. As an alternative solution, a photodegradation method was developed using photocatalyst material assisted by ultraviolet irradiation. In this photodegradation method, dye substances are broken down into components that are simpler and safer for the environment. The possibility of using sunlight as a radiation source makes this a particularly promising method for countries such as Indonesia. Procion red, one of the most commonly utilized synthetic dyes in the home textile or Batik industry, was used as a model pollutant in this study. The objectives of the present research were to synthesize and characterize a nano-photocatalyst of ZnO-natural zeolite with the capacity to degrade Procion red. This nano-photocatalyst was synthesized using the sol-gel method, by which Zn(CH3COO)2 2H2O was used as a precursor and combined with natural zeolite to increase its photocatalytic ability. The nano-photocatalyst was characterized using X-ray diffraction (XRD), scanning electron microscope/energy dispersive X-ray spectroscopy (SEM/EDX), and Brunauer-Emmett-Teller (BET). The activity of nano-photocatalyst ZnO-natural zeolite was compared to ZnO alone and natural zeolite alone in terms of its ability to degrade Procion red. An average photocatalyst crystallite diameter of 82 nm was achieved, proving that a nano-sized photocatalyst of ZnO-natural zeolite was successfully synthesized. BET characterization showed that nano-photocatalyst ZnO-natural zeolite had a specific surface area of 14.84 m2/g, a pore size of 32.71 nm, and a pore volume of 0.12 cm2/g. A peak Procion red degradation percentage of 96.23% was obtained using nano-photocatalyst ZnO-natural zeolite after 120 minutes of irradiation under sunlight applied to a Procion red concentration of 50 ppm.